Rapid repair techniques for severely earthquake-damaged circular bridge piers with flexural failure mode - Sun, Z.; Li, H.; Bi, Kaiming; Si, B.; Wang, D. (Springer New York LLC, 2017)
© 2017, Institute of Engineering Mechanics, China Earthquake Administration and Springer-Verlag Berlin Heidelberg. In this study, three rapid repair techniques are proposed to retrofit circular bridge piers that are severely damaged by the flexural failure mode in major earthquakes. The quasi-static tests on three 1:2.5 scaled circular pier specimens are conducted to evaluate the efficiency of the proposed repair techniques. For the purpose of rapid repair, the repair procedure for all the specimens is conducted within four days, and the behavior of the repaired specimens is evaluated and compared with the original ones. A finite element model is developed to predict the cyclic behavior of the repaired specimens and the numerical results are compared with the test data. It is found that all the repaired specimens exhibit similar or larger lateral strength and deformation capacity than the original ones. The initial lateral stiffness of all the repaired specimens is lower than that of the original ones, while they show a higher lateral stiffness at the later stage of the test. No noticeable difference is observed for the energy dissipation capacity between the original and repaired pier specimens. It is suggested that the repair technique using the early-strength concrete jacket confined by carbon fiber reinforced polymer (CFRP) sheets can be an optimal method for the rapid repair of severely earthquake-damaged circular bridge piers with flexural failure mode.